Study of the Rate of Corrosion of Steel 20 in the Presence of Increased Content of Organic Chlorinous Compounds in Oil - Gazrati, I.B.; Vansinvin, N.Z.; Nefedov, A.N.; Akurpekova, A.K.; Abilmagzhanov, A.Z. (Journal of Applied Solution Chemistry and Modeling, 2022)
The paper presents data on the corrosion rate of steel 20 in the presence of organochlorine compounds in the oil. It is shown that with an increase in the concentration of organochlorine compounds, the corrosion rate of steel increases. It was found that with the addition of an inhibitor at CCl4 concentrations of 0.01 and 0.05%, the corrosion rate decreases, while at a CCl4 concentration of 0.03%, the corrosion rate does not change.